Development status and challenges of LEO IoT - Geng-xin ZHANG; Xiao JIE; Zhi-cheng QU (物联网学报)
According to the requirements of interconnection of all things,background of development of establishing IoT using the LEO satellite communication network is researched.The development status of LEO IoT at home and abroad is analyzed,and the technical challenges and research content of LEO IoT are discussed.